Supply Chain Cnalysis Of Edamame As The Leading Soybeans In Jember - Qory Zuniana; Tidar Aden Hawa (AGRIBEST, 2020)
Edamame is a Japanese soybean that is very popular in Indonesia. The requirement for edamame to grow is that the weather is quite hot with relatively high rainfall. Edamame is a type of vegetable, so edamame must be processed directly in the form of frozen and ready to eat or frozen ready to eat. The soybean marketing channel as a superior product of Jember Regency needs to be known by consumers through the supply chain. The concept of supply chain (supply chain) is one of the appropriate approaches used to solve the problem of consumer demand for soybean commodities. The research objectives include; 1) Tracking edamame soybean supply chain activities as superior soybeans in Jember Regency, and 2) Comparing efficiency in each supply chain of edamame soybean commodity as leading commodities in Jember Regency. The method used in this research is descriptive method and the data used are primary data and secondary data. To answer the purpose of the first research, a descriptive analysis was carried out and the second objective was answered using a marketing margin analysis tool. The results of the study revealed that 1. Edamame soybean supply chain activities are from edamame soybean farmers who partner with PT Mitra Tani then processed by PT Mitra Tani after being processed until the final product is marketed through the domestic and international markets to the final consumer. 2) The most efficient distribution of marketing margins occurred in 2014 where industry margins were balanced by farmer shares.